EDUKASI PERTOLONGAN PERTAMA PADA KEGAWATDARURATAN CEDERA OLAHRAGA UNTUK MENINGKATKAN KESIAPSIAGAANSISWA SEKOLAH DASAR DI MEDAN - Handerman Vitu; Ika Ariyanti; Ahmad Wildan Afifi; Erita Gustina; Jessika Caroline; Launa Kasri Br Ketaren (MAJU : Indonesian Journal of Community Empowerment, 2026)
Elementary school students are at risk of sports-related injuries during physical education, extracurricular activities, and play, while their knowledge of appropriate first aid remains limited. This community service program aimed to improve students' preparedness in providing basic first aid for sports injuries at SD Negeri 060801 Medan. The program was conducted through health education using lectures, interactive discussions, demonstrations, and simulation of first aid procedures for common sports injuries. Educational media and simple first aid equipment were utilized to facilitate students' understanding and active participation. The evaluation results showed an improvement in students' knowledge and preparedness to recognize sports injuries, perform appropriate initial responses, and seek assistance from teachers or health personnel when necessary. The program also increased students' awareness of the importance of safe behavior during sports activities. This educational intervention is expected to support the development of a safer and more prepared school environment in managing sports-related emergencies.